Decreased cerebral perfusion in Duchenne muscular dystrophy patients - Doorenweerd, Nathalie; Dumas, Eve M.; Ghariq, Eidrees; Schmid, Sophie; Straathof, Chiara S.M.; Roest, Arno A.W.; Wokke, Beatrijs H.; van Zwet, Erik W.; Webb, Andrew G.; Hendriksen, Jos G.M.; van Buchem, Mark A.; Verschuuren, Jan J.G.M.; et al. (Neuromuscular disorders : NMD, 2017)
•We performed the first cerebral perfusion MRI in DMD and age-matched control boys.•Globally reduced perfusion was found in DMD by on average 17%.•Reduced cerebral perfusion was independent of the reduced grey matter volume. Duchenne muscular dystrophy is caused by dystrophin gene mutations which lead to the absence of the protein dystrophin. A significant proportion of patients suffer from learning and behavioural disabilities, in addition to muscle weakness. We have previously shown that these patients have a smaller total brain and grey matter volume, and altered white matter microstructure compared to healthy controls. Patients with more distal gene mutations, predicted to affect dystrophin isoforms Dp140 and Dp427, showed greater grey matter reduction. Now, we studied if cerebral blood flow in Duchenne muscular dystrophy patients is altered, since cerebral expression of dystrophin also occurs in vascular endothelial cells and astrocytes associated with cerebral vasculature. T1-weighted anatomical and pseudo-continuous arterial spin labeling cerebral blood flow images were obtained from 26 patients and 19 age-matched controls (ages 8–18 years) on a 3 tesla MRI scanner. Group comparisons of cerebral blood flow were made with and without correcting for grey matter volume using partial volume correction. Results showed that patients had a lower cerebral blood flow than controls (40.0 ± 6.4 and 47.8 ± 6.3 mL/100 g/min respectively, p = 0.0002). This reduction was independent of grey matter volume, suggesting that they are two different aspects of the pathophysiology. Cerebral blood flow was lowest in patients lacking Dp140. There was no difference in CBF between ambulant and non-ambulant patients. Only three patients showed a reduced left ventricular ejection fraction. No correlation between cerebral blood flow and age was found. Our results indicate that cerebral perfusion is reduced in Duchenne muscular dystrophy patients independent of the reduced grey matter volume.